Tailoring Oxygen Vacancies of BiVO4 toward Highly Efficient Noble‐Metal‐Free Electrocatalyst for Artificial N2 Fixation under Ambient Conditions. Issue 6 (15th November 2018) - Yao, Jia‐Xin; Bao, Di; Zhang, Qi; Shi, Miao‐Miao; Wang, Yue; Gao, Rui; Yan, Jun‐Min; Jiang, Qing
Abstract: Ammonia (NH3 ) is vital to human beings as an important energy carrier, fertilizer precursor, and fuel, while breakage of the NN bond in nitrogen (N2 ) is a kinetically complex and energetically challenging multistep reaction. Development of electrocatalysts for efficient NH3 electrosynthesis via the N2 reduction reaction (NRR) is highly desirable but remains a key challenge. In this work, based on the density functional theory calculations, a novel and effective strategy to boost the nitrogen electroreduction performance of BiVO4 by tailoring its oxygen vacancies (OVs) is first proposed and demonstrated. Unexpectedly, the noble‐metal‐free BiVO4 with the highest OVs concentration shows excellent NRR performances, including high NH3 yield rate (up to 8.60 µg h −1 mg −1 cat. ), high faradaic efficiency (10.04% at −0.5 V vs reversible hydrogen electrode), and good stability (up to 24 h) at ambient conditions, outperforming most reported NRR electrocatalysts under ambient conditions and even some under harsh conditions, which can be attributed to enhanced N2 adsorption energy and a more favorable active reaction site at the V atom with lower coordination and higher spin‐polarization with a localized magnetic moment due to the introduction of OVs. Abstract : Non‐noble metal semiconductor BiVO4 along with different oxygen vacancies (OVs) concentrations is obtained by a facile hydrothermal synthesis. Based on the theoretical calculations, the optimum BiVO4 (pH = 7) sample presents brilliant N2 reduction reaction electrocatalytic performance under ambient conditions owing to the enhanced N2 adsorption energy and more favorable active reaction site at the V atom due to the introduction of OVs.